Pentoxifylline Inhibits WNT Signalling in β-Catenin(high) Patient-Derived Melanoma Cell Populations - Talar, Beata (PLoS One, 2016)
BACKGROUND: The heterogeneity of melanoma needs to be addressed and combination therapies seem to be necessary to overcome intrinsic and acquired resistance to newly developed immunotherapies and targeted therapies. Although the role of WNT/β-catenin pathway in melanoma was early demonstrated, its contribution to the lack of the melanoma patient response to treatment was only recently recognized. Using patient-derived melanoma cell populations, we investigated the influence of pentoxifylline on melanoma cells with either high or low expression of β-catenin. FINDINGS: Our results indicate that pentoxifylline inhibits the activity of the canonical WNT pathway in melanoma cell populations with high basal activity of this signalling. This is supported by lowered overall activity of transcription factors TCF/LEF and reduced nuclear localisation of active β-catenin. Moreover, treatment of β-catenin(high) melanoma cell populations with pentoxifylline induces downregulation of genes that are targets of the WNT/β-catenin pathway including connective tissue growth factor (CTGF) and microphthalmia-associated transcription factor (MITF-M), a melanocyte- and melanoma cell-specific regulator. CONCLUSIONS: These results suggest that pentoxifylline, a drug approved by the FDA in the treatment of peripheral arterial disease, might be tested in a subset of melanoma patients with elevated activity of β-catenin. This pharmaceutical might be tested as an adjuvant drug in combination therapies when the response to immunotherapy is prevented by high activity of the WNT/β-catenin pathway.